Return the night - Tan, Whitney Yuin Wen (Nanyang Technological University, 2021)
This FYP report is a documentation of my year-long journey working on the film “RETURN THE NIGHT”. It details my creative and technical processes over the year, from pitching of the film to production and finally down to festival strategies. In specificity, the report covers my journey as a writer-director for the film, touching upon my approach and execution towards the story, detailing the process in which it went through to mature and morph into the final piece. The report strives to provide insight to the explorations and challenges I face as a director in the process of filmmaking to push my creative boundaries. It also aims to highlight the multi layered nature of a collaborative art form such as film.